Information System For New Residents Registration Based On Web and Android: Sistem Informasi Pendataan Warga Baru Berbasis Web dan Android - Shiddiq, Zulfian Syahril; Rosid, Mochamad Alfan; Fitrani, Arif Senja; Hindarto, Hindarto (Procedia of Engineering and Life Science, 2023)
The Suko Village is one of 24 villages in the Sidoarjo sub-district, Suko village is the second most populous village in the Sidoarjo sub-district, reaching 15 thousand people spread over 72 RTs. Geographically, the Suko village area is in the middle of the city which has led to many housing developments that have made Suko village a densely populated settlement, as well as a destination for residents outside the city of Sidoarjo to stop by and settle down.The purpose of this research is to design a Information System For Registration New Residents Based On Web and Android that can be accessed. The research method used is the waterfall method, while the technique for collecting data uses observation and interview techniques. The result of this research is to make the village government aware of all its citizens, including those who live not permanently and can record citizens efficiently and no longer use a manual system.